The Effect of Interval Training on Increasing Cardiorespiratory Endurance in Futsal Extracurricular - Candra, Dicki; Haqiyah, Aridhotul; Iskandar, Tatang; Abidin, Dindin (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to determine the effect of interval training exercises on increasing cardiorespiratory endurance. The research method used in this study is the experimental method. The population in this study is students who are members of the futsal extracurricular of Tunas Harapan Junior High School, which amounts to 32 people, The sampling technique uses total sampling where all populations are used as samples. The instrument used by the author in this study is a multistage running test. The test results showed that the significance value (2-tailed) was 0.000, which was smaller than the significance level of 0.05 (p < 0.05). The results of the average score comparison showed that the interval training group had an average of 46,162, while the conventional group had an average of 37,008. The results of this study showed that Tunas Harapan Junior High School futsal players experienced a significant increase in cardiorespiratory endurance after undergoing an interval training program.